CYTOTOXICITY OF P-123-HYPERICIN PHOTODYNAMIC INACTIVATION ON HUMAN CELLS LINE - CONRADO, Pollyanna Cristina Vincenzi (2019)
Photodynamic inactivation (PDI) is a non-invasive technology, recognized since 1900, that uses a combination of a light source and a photosensitizer (PS), causing photochemical reactions. Hypericin (Hyp) is a napthodianthrone naturally isolated compound, with promising photodynamic properties by high penetration and absorption. A novel formulation was developed the encapsulated Hyp in P-123 copolymeric micelles (P123-Hyp) formed at low copolymeric concentration, with the intention to improve the photodynamic characteristics of Hyp. Therefore, its necessary evaluate if PDI mediated P-123-Hyp cause cytotoxicity in cell line human. For this, assay was performed to evaluate the action of photoinactivation on keratinocytes in vitro. In cytotoxicity assay, Keratinocytes cells were incubated with concentrations of P-123-Hyp (0.09 - 50 μmol/L) for 2 h in the dark at 37ᐤC in 0.5% CO2, subsequently the cells were irradiated with LED at 27 J/cm2 . Then, post-irradiation keratinocytes were re-incubated for 24h in the dark at 37ᐤC in 0.5% CO2. The cell viability were evaluated with MTS, compared to untreated control. The results demonstrated non-cytotoxic in cells at concentrations ranging 0.78 - 50 μmol/L, and slight cytotoxicity in concentrations 0.09 - 0.39 μmol/L of P-123-Hyp. Thus, this study showed that the use of P-123-Hyp-PDI is safe promising treatment to several diseases.